Risk factors for decline in Montreal Cognitive Assessment (MoCA) scores in patients with acute transient ischemic attack and minor stroke. Issue 7 (7th June 2022) - Zuo, Lijun; Dong, YanHong; Liao, Xiaoling; Pan, Yuesong; Xiang, Xianglong; Meng, Xia; Li, Hao; Zhao, Xingquan; Wang, Yilong; Shi, Jiong; Wang, Yongjun
Abstract: Cognitive impairment after stroke/transient ischemic attack (TIA) has a high prevalence. The authors aimed to explore the risk factors for declined cognitive function with Montreal Cognitive Assessment (MoCA)‐Beijing in patients with stroke/TIA at acute phase. Total 2283 patients with acute stroke/TIA without a history of dementia were assessed at 2 weeks of onset. Patients were assessed by MoCA‐Beijing on day 14 and at 3 months follow‐ups. Cognitive impairment was defined as MoCA‐Beijing ≤22. Patients' cognitive status was considered as declined if there were a reduction of ≥2 points in MoCA‐Beijing score and patients were considered to have improved if there were an increase of ≥2 points. The score of MoCA‐Beijing was considered to be stable if there were an increase or decrease of 1 point. Most patients were in 60 s (60.96 ± 10.75 years old) with a median (interquartile range) National Institute of Health Stroke Scale score of 3.00 (4.00) and greater than primary school level of education, and 1657 participants (72.58%) were male. Cognitive evaluation was conducted in 2283 of 2625 patients (82.70%) with MoCA‐Beijing at baseline. Total 292 (12.79%) patients have a cognitive decline at 3 months, 786 (34.42%) patients were stable and 1205 (52.78%) patients were improved. In the logistic regression, a history of hypertension was associated with cognitive deterioration from baseline to 3‐month. Patients with a history of hypertension have a higher risk for cognitive deterioration from baseline to 3‐month after stroke/TIA.